A new classification of wind instruments: Orofacial considerations - Miguel Clemente; Joaquim Mendes; André Moreira; Gilberto Bernardes; Henk Van Twillert; Afonso Ferreira; José Manuel Amarante (Elsevier, 2019)
Background/objective: Playing a wind instrument implies rhythmic jaw movements where the embouchure applies forces with different directions and intensities towards the orofacial structures. These features are relevant when comparing the differences between a clarinettist and a saxophone player embouchure, independently to the fact that both belong to the single-reed instrument group, making therefore necessary to update the actual classification. Methods: Lateral cephalograms were taken to single-reed, double-reed and brass instrumentalists with the purpose of analyzing the relationship of the mouthpiece and the orofacial structures. Results: The comparison of the different wind instruments showed substantial differences. Therefore the authors purpose a new classification of wind instruments: Class 1 single-reed mouthpiece, division 1- clarinet, division 2 -saxophone; Class 2 double-reed instruments, division 1- oboe, division 2- bassoon; Class 3 cup-shaped mouthpiece, division 1- trumpet and French horn, division 2- trombone and tuba; Class 4 aperture mouthpieces, division 1- flute, division 2 - transversal flute and piccolo. Conclusions: Elements such as dental arches, teeth and lips, assume vital importance at a new nomenclature and classification of woodwind instruments that were in the past mainly classified by the type of mouthpiece and not taking into consideration its relationship with their neighboring structures.